The Existence of "Manre Bale Bungo" Belief in Community Creed viewed from the perspective of Islamic religious education - Fatmawati (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This research aims to determine the community's perception of the existence and influence of the "manre bale bungo" (eating bungo fish) belief on community beliefs from the perspective of Islamic religious education in Sumpabaka Hamlet, Pasaka Village, Sabbangparu District, Wajo Regency. The method used in this research uses descriptive-qualitative research. With data collection procedures using field research (Field Research), Data collection techniques were carried out by conducting observations, interviews, and documentation. Technical data analysis is carried out using steps, namely data reduction, data presentation, conclusions, and verification. Descriptive-qualitative research is a type of research that describes events, phenomena, and conditions that occur in the field. The research results state that the public's perception regarding "bale bungo" is as a form of respect for the culture of their ancestors by not consuming bale bungo. The influence of public belief in "bale bungo" is that it gives rise to fanatical attitudes, which are divided into fanatics in social practices and fanatics in religious practices, as well as being the subject of further study from the perspective of Islamic religious education.